Work hard play hard: exploring alcohol consumption among student-athletes - Rodgers, Joseph (Kansas State University, 2014)
Collegiate student-athletes have been identified as an especially at-risk subgroup for heavy alcohol use as compared to the general college student population. Despite the intense physical demands required for athletic participation, national studies have found that intercollegiate athletes consumed more alcohol, engaged in more frequent heavy episodic drinking, and experienced more negative alcohol-related consequences as compared with non-athletes. A combination of structured open-ended and closed-ended questions was used in the current study. Data was collected from student-athletes across the United States through semi-structured, individual interviews informed by the theory of planned behavior (Ajzen, 1991) and its constructs (attitudes, subjective norms, and perceived behavioral control). Open coding was the chosen method for data analysis for the study. Codes, accompanied by descriptives, were organized into themes as they related to the research questions and the theory of planned behavior. Results show that nearly half (49%) of student-athletes report drinking five or more drinks in one-sitting, with the majority of student-athletes consuming alcohol only 1-2 times per week at parties. Student-athletes’ attitudes towards heavy drinking and alcohol outcome expectancies are apparent in two themes: sexual risk taking and athletic training justification. Many respondents expressed alcohol-drinking relationships with other student-athletes at their institution. The NCAA has recognized the importance of addressing alcohol related issues among collegiate athletes. However, the type of educational programming being assigned by the NCAA has been generally ineffective in reducing alcohol use of student-athletes. In fact, of the student-athletes surveyed in this study, the majority struggled with recalling NCAA alcohol prevention programs that they are familiar with—only 13% of student-athletes use alcohol prevention skills and tools taught by the NCAA or their athletic department to reduce alcohol consumption. Similarly, there is a belief among student-athletes that the NCAA is not doing enough to reduce alcohol use among student-athletes is exemplified by the fact that the majority (57%) gave the NCAA an F letter-grade for their current alcohol intervention and prevention strategies that are being taught to student-athletes. Although the NCAA requires student-athletes to participate in alcohol, tobacco and other drug education programming, only approximately 25% of student-athletes surveyed recalled viewing a NCAA drug and alcohol educational video or reading a brochure detailing the effect alcohol has on athletic performance at the beginning of the academic year. Furthermore, 85% of student-athletes reported that they were not informed of the counseling or alcohol treatment options that the NCAA provides.
Keywords: Alcohol; Student-athletes; NCAA; Theory of planned behavior; Mass Communications (0708)